Inhibiting Factors of Acquisition of Library Materials and Services Provision to Users in Special Libraries - Akanbi, Mohammed Lawal; Sambo, Atanda Saliu (Ghana Library Journal, 2022)
The study investigated the inhibiting factors of the acquisition of library materials and services provided to users in special libraries. In carrying out this study three research questions were posed. A social survey research design was adopted for the study. The population of the study comprised librarians and para-professional staff working in the special libraries. Descriptive statistics were used to analyze data using frequency counts, tables and percentages. The findings showed that the libraries face diverse problems in the acquisition of library materials. These include lack of acquisition policy, inadequate funds, high cost of foreign materials, poor quality of locally published materials, poor communication services, poor bibliographic control and poor management of funds. It also revealed that several factors were found to be militating against the effective provision of library service delivery to users in the selected special libraries. These include lack of Information and Communication Technology tools and compliance, inadequate funding, poor infrastructure and inadequate human resources.